BET 2: Is there an association between iodine, shellfish and contrast agent allergies?. Issue 11 (22nd October 2019) - Long, Benjamin; Chassee, Todd; Jones, Jeffrey S
Abstract : A shortcut review was carried out to establish whether having a shellfish or iodine allergy changed the risk of allergic reaction in patients receiving radiocontrast medium more than other concomitant allergies. One relevant paper (a systematic review) was identified for inclusion using the reported search strategy. The author, date and country of publication; group studied; study type; relevant outcomes; results and study weaknesses of this paper are tabulated. It is concluded that there is no evidence that allergy to shellfish or iodine alters the risk of reaction to intravenous contrast more than any other allergies.